Citizen Training and Initial Education: Case Study in Chile - Muñoz Griffith, Vicente; Molina Martínez, Rolando (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The article aims to identify and analyze the knowledge possessed by Preschool Educators who work at Transition Level II (Kindergarten), referring to Citizenship Education, and how this knowledge is subsequently transformed into pedagogical strategies that are implemented in the classroom. The data collection was carried out by means of two instruments, a qualitative questionnaire and a semi-structured interview, the results obtained allowed to demonstrate the level of knowledge that the Preschool Educators possess regarding Citizenship Training, in addition to knowing the pedagogical strategies that they use in the classrooms with the toddlers of NT2.